Pure and zirconium-doped manganese(II,III) oxide: Investigations on structural and conduction-related properties within the Lattice Compatibility Theory scope - YUMAK YAHŞİ, AYŞE (ELSEVIER SCI LTD, 2015)
Manganese(II,III) oxide Mn3O4 thin films have been deposited on glass substrates using a simple spray pyrolysis method. Zirconium doping protocol was applied in order to verify some recently claimed enhancements of hausmannite physical properties. Gradual doping was achieved with ratio [Zr]/[Mn] = 1%, 2% and 3% in addition to pure Mn3O4. Beyond classical characterization techniques, effects of Zr-doping were studied in reference to the expected use in rechargeable batteries and sensing devices. Moreover, additional opto-thermal investigation and analyses of the Lattice Compatibility Theory led to a founded understanding to the dynamics of Zirconium ion incorporation inside Mn3O4 host matrices. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Mn3O4; Spray pyrolysis; Optical constants; Zirconium doping; Lattice Compatibility Theory (LCT); THIN-FILMS; ELECTRICAL-PROPERTIES; DIELECTRIC-PROPERTIES; SPATIAL EVOLUTION; EXPANSION; TEMPERATURE; PROTOCOL; MODEL